Seasonal incidence of insect pests of mustard under temperate ecosystem of Kashmir - Hydari, Asgar Ali; Sheikh, Tahir Ahmad; Yaqoob, Munazah; Wani, Fahim Jeelani; Hussain Mir, Sajad (Indian Journal of Plant Protection, 2025)
The study of mustard insect pests during the Rabi season of 2021-22 identified five major pests and examined their correlation with various weather parameters. The insect pests identified on brown sarson include the cabbage aphid, cabbage butterfly, diamondback moth, mustard beetle, and leaf miner. Additionally, five minor pests were observed viz., mustard sawfly, mustard aphid, green peach aphid, shield bug, and red squash bug. The incidence diamondback moth, cabbage butterfly, mustard beetle and leaf miner commenced from 10th standard meteorological week. The population gradually increased and reached peak on 19th standard meteorological week with a population of 6.67, 21.33, 4.67 and 5.00 respectively, and declined afterwards. The correlation data revealed that maximum temperature, minimum temperature, rainfall, relative humidity and sunshine hours were positively correlated with diamondback moth, cabbage butterfly, mustard beetle and pea leaf miner whereas rainfall and relative humidity were negatively correlated with cabbage butterfly and mustard beetle. B. brassicae first appeared on the crop during 10th standard meteorological week (0.67aphid/plant) and the infestation of L. erysimi was observed from 11th standard meteorological week (2.13aphid/plant). M. persicae appeared on the crop late in 14th standard meteorological week (1.33 aphid/ plant). The incidence of B. brassicae, L. erysimi and M. persicae reached peak on 19th standard meteorological week with a population of 106.67, 14.45, and 12.33 (aphid/ plant) respectively.